Eksplorasi Penggunaan Warna Biru dalam Membangun Brand Tone Museum Radya Pustaka di Instagram - Pandanwangi, Brilindra; Dewi, Hanifa Noviari (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2025)
This study examines the visual communication strategy of Museum Radya Pustaka Surakarta in the digital era, focusing on the consistency of blue as the main brand tone element on the museum’s official Instagram account. The research employs a qualitative approach with descriptive analysis of three selected posts that represent persuasive elements, interactivity, and visual strength. The findings indicate that the implementation of two-way communication through interactive content, the consistent application of blue color psychology, and the optimization of Nudge Theory are effective in increasing engagement and participation within the museum’s digital community. The use of blue not only strengthens the museum’s visual identity and credible image but also creates a positive emotional experience for the audience. These results underscore the importance of adaptive, participatory, and color psychology-based visual communication strategies in building engagement and maintaining the museum’s relevance amid digital transformation. This research is expected to serve as a reference for other institutions in developing effective visual communication on social media.